Alternate stabilization methods for CZTSSe photovoltaic devices by thermal treatment, dark electric bias and illumination. (October 2022) - Ananda, W.; Rennhofer, M.; Mittal, A.; Zechner, N.; Lang, W.
Abstract: Reliable measurement routines are crucial for power rating and yield prediction of photovoltaic emerging thin-film technologies. Copper-Zinc-Tin-Sulfur-Selenium (CZTSSe) thin-film photovoltaic devices are an emerging technology made of abundant elements. Still, sufficient stabilization methods prior to electric power measurement are missing in the international standardization, while existing standards for other thin-film technologies do not work properly for CZTSSe. This study investigated methods for achieving power stabilization of the CZTSSe solar devices. Three complementary stabilization routines for the kesterite-based solar devices were investigated as an alternative to the existing international device testing standards: rapid annealing, dark electric biasing and different operating points under illumination. The typical number of stabilization cycles for power stabilization was between 3 and 6 cycles of rapid annealing, dark electric bias and illumination with a power loss of -19.5%, -11.4%, and -1.9%, for the respective methods. The dark electric bias method was found to provide the most reliable average result for power stabilization. All stabilization methods proved to have the potential to work sufficiently in stabilizing the CZTSSe devices for standardized power measurement. Highlights: Stabilization of CZTSSe solar devices: rapid annealing, dark-biasing, illumination. While promising, rapid annealing at T ≤ 100 °C leads to strong degradation. Dark bias at T > 25 °C and current bias < 0.66 Isc gives fast stabilization. The best illumination method is stabilization based on IEC 61215-2 but with 25 °C. All methods allow to stabilize devices with the 2% criterion of the standard.